PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INTI INDO SAWIT SUBUR DESA BULIAN JAYA KECAMATAN MARO SEBO ILIR KABUPATEN BATANG HARI - Etty Siswati (Universitas Batanghari Jambi, 2017)
The purpose of this study was to determine .Partially Effect of work environment to employees performance at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari . Partially Effect of work discipline on the performance of employees at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. Simultaneously the influence of the working environment and work discipline on the performance of employees at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. The data were analyzed using multiple linear regression and tools using SPSS 20.0 for windows. The results showed that partially (1) work environment (X1) has a positive effect on the performance of employees at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. By using t test showed tcount 3,011 > 1,649 ttabel, then Ho is rejected. (2) work discipline (X2) has a positive and significant impact on the performance of employees at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. Based on the t test results showed the value of tcount 3,316 > 1,649 ttabel, then Ho is rejected. Then simultaneously by using F test showed that the value of fcount = 15:13 > ftable = 2.76. So that the working environment (X1) and work discipline (X2) has a positive effect on employee performance (Y) at PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari.Key word: Work environment, Work discipline, Employees performance PT. Inti Indo Sawit Subur Desa Bulian Jaya Kecamatan Maro Sebo Ilir Kabupaten Batang Hari